Mihin pankkiunionia tarvitaan?; Why Do We Need a Banking Union? - Antti Suvanto; Kimmo Virolainen (The Research Institute of the Finnish Economy (ETLA), 2014)
– The project to build up a banking union in Europe was launched in summer 2012. Thereafter the progress has been fast. Single Supervisory Mechanism will embark on November 1, 2014. A decision on the Single Resolution Mechanism was made in Spring 2014. It should be up and running as of the beginning of 2015. The main rationalisation for the banking union has been the aspiration to to break the vicious circle between banks and sovereigns. Equally important rationalization is to safeguard the smooth operation of the single market. If the cross-border banking is significant, home-country supervision is no more sufficient. If banks become, thanks to large-scale cross-border operations, very large in relation to the economic size of the home country, the interdependence of the banks and the sovereign increases. The greatest challenge of the banking union project in the coming years is to build up both the capacity and the credibility. The first test is the successful execution of the asset quality review of the bank balance sheets and the subsequent stress tests. The new supervisory mechanism needs to prove that neither national interests nor lobbying by major financial institutions have any influence on its decisions.
Keywords: F15; G21; G28; 330; Banking union; Financial supervision; Bank resolution; Single market